Examination of the hippocampal contribution to serotonin 5-HT2A receptor-mediated facilitation of object memory in C57BL/6J mice. (October 2016) - Zhang, Gongliang; Cinalli, David; Cohen, Sarah J.; Knapp, Kristina D.; Rios, Lisa M.; Martínez-Hernández, José; Luján, Rafael; Stackman, Robert W.
Abstract: The rodent hippocampus supports non-spatial object memory. Serotonin 5-HT2A receptors (5-HT2A R) are widely expressed throughout the hippocampus. We previously demonstrated that the activation of 5-HT2A Rs enhanced the strength of object memory assessed 24 h after a limited (i.e., weak memory) training procedure. Here, we examined the subcellular distribution of 5-HT2A Rs in the hippocampal CA1 region and underlying mechanisms of 5-HT2A R-mediated object memory consolidation. Analyses with immuno-electron microscopy revealed the presence of 5-HT2A Rs on the dendritic spines and shafts of hippocampal CA1 neurons, and presynaptic terminals in the CA1 region. In an object recognition memory procedure that places higher demand on the hippocampus, only post-training systemic or intrahippocampal administration of the 5-HT2A R agonist TCB-2 enhanced object memory. Object memory enhancement by TCB-2 was blocked by the 5-HT2A R antagonist, MDL 11, 937. The memory-enhancing dose of systemic TCB-2 increased extracellular glutamate levels in hippocampal dialysate samples, and increased the mean in vivo firing rate of hippocampal CA1 neurons. In summary, these data indicate a pre- and post-synaptic distribution of 5-HT2A Rs, and activation of 5-HT2A Rs selectively enhanced the consolidation of object memory, without affecting encoding or retrieval. The 5-HT2A R-mediated facilitation of hippocampal memory may be associated with an increase in hippocampal neuronal firing and glutamate efflux during a post-training time window in which recently encoded memories undergo consolidation. Highlights: 5-HT2A Rs are expressed on the dendritic spines and shafts, and presynaptic terminals of hippocampal CA1 neurons. Activation of hippocampal 5-HT2A R enhances consolidation of object memory in mice. Activation of 5-HT2A R enhances hippocampal glutamate release and firing rates of CA1 neurons.